Relative growth and morphometry of sagittae otoliths of weakfishes, Cynoscion guatucupa (Cuvier, 1830) and Cynoscion jamaicensis (Vaillant & Bocourt, 1883), in the Southwestern Atlantic Ocean, Brazil (Ocean and Coastal Research, 2022)
The weakfishes, Cynoscion guatucupa and C. jamaicensis, are important demersal fishery resources and are targeted by multifleet operations in the Southwest Atlantic. This study describes the length-weight relationships between sagittae otoliths (length-OL, height-OH, thickness-OT, and weight-OWT) and the sizes of the fish (total length-LT, standard length-LS, and total weight-WT). The proportion between otolith length and height (aspect ratio-OAR) was also compared between species. The samples were obtained monthly from March 2017 to February 2018 from small-scale commercial fisheries from landings of bottom trawls and gillnets on the continental shelf in the Rio de Janeiro state, southeastern coast of Brazil. The ANCOVA did not indicate significant diferences in relative growth between sexes for both species (p > 0.05) while the length frequency was diferent (p < 0.001). Cynoscion guatucupa showed positive allometry, WT = 4E-06LT3.21 and C. jamaicensis negative allometry, WT = 2E-05LT2.90 (p < 0.05). Both species showed diferences in the condition factor between the sexes (p < 0.05). Significant diferences were observed in the measurements of the otoliths between the two species (p < 0.001). All regressions between fish measurements and otolith morphometry were highly significant (p < 0.001) for both species. The best estimates of fish size and weight were related to the otolith length: OL vs LT (r2 = 0.93; 0.96); OL vs LS (r2 = 0.92; 0.96); OL vs WT (r2 = 0.91; 0.93) for C. guatucupa and C. jamaicensis, respectively. This information adds useful biological data for multiple types of studies, e.g., food ecology (prey-predator), age and growth, reproduction, fisheries assessment and long-term landing monitoring. Our results confrmed the historical pattern of relative growth, supporting that otolith growth reflects the somatic growth of weakfishes in the study area, reinforcing the importance to determine these reference points.